2013
DOI: 10.1108/09564231311323962
|View full text |Cite
|
Sign up to set email alerts
|

Measuring consumer perceptions of online shopping convenience

Abstract: PurposeThe purpose of this paper is to identify the key convenience dimensions of online shopping, as convenience has been one of the principal motivations underlying customer inclinations to adopt online shopping.Design/methodology/approachThe authors first employ in‐depth focus group interviews with online consumers to identify the attributes of online shopping convenience and then develop and validate an instrument of five key dimensions to measure online shopping convenience by analyzing data collected via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
381
0
20

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 382 publications
(419 citation statements)
references
References 56 publications
18
381
0
20
Order By: Relevance
“…Mpinganjira [16] recommended four dimensions: search, evaluation, order, and possession convenience, whereas Roy et al [21] analyzed five service convenience types, including decision, access, transaction, benefit, and post-benefit. These dimensions are similar to those found in, and the variables were also based on Jiang et al [15]. For the above-mentioned reasons, the concept of convenience in this study is based on five the convenience dimensions proposed by Jiang et al [15].…”
Section: Conveniencementioning
confidence: 55%
See 3 more Smart Citations
“…Mpinganjira [16] recommended four dimensions: search, evaluation, order, and possession convenience, whereas Roy et al [21] analyzed five service convenience types, including decision, access, transaction, benefit, and post-benefit. These dimensions are similar to those found in, and the variables were also based on Jiang et al [15]. For the above-mentioned reasons, the concept of convenience in this study is based on five the convenience dimensions proposed by Jiang et al [15].…”
Section: Conveniencementioning
confidence: 55%
“…Beauchamp and Ponder [9] offered four components of convenience: access, search, transaction, and possession convenience, when considering the customer's perception of convenience in the online and traditional shopping environments. However, Jiang et al [15] suggested that the dimensions and variables involved in Beauchamp and Ponder [9] did not reflect the unique characteristics of online shopping. Therefore, based on studies of Berry et al [12] and Seiders et al [18,20], Jiang et al [15] identified salient online shopping convenience dimensions, and developed a valid online shopping convenience measurement instrument.…”
Section: Conveniencementioning
confidence: 99%
See 2 more Smart Citations
“…According to Jiang, Yang and Jun [3], "as consumers allocate less time to shopping and more to other endeavors, their desire for convenience has mounted and their attention has been frequently diverted to virtual shopping as an alternative medium". Even, their research showed that there are five dimensions of online shopping convenience, which are access, search, evaluation, transaction, and possession/post-purchase convenience.…”
Section: )mentioning
confidence: 99%